Przyszłość nauki, przyszłość uniwersytetu. Fantastycznonaukowe prognozy zaniku wiedzy naukowej - Brzostek, Dariusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The predictions of science fiction play an important part in the cultural landscape of contemporary western culture, being integral to the popular culture (novels, movies, TV series, graphic novels). Science fiction narratives predict the future of society, technology, culture but also – the science itself and a university as a scientific institution. The aim of this work is to shed light on the depiction of the future of science, knowledge, and university in the science fiction works, predicting the ineluctable societal collapse. The essay focuses on the use of the scientific discourse and scientific knowledge in the chosen science fiction narratives by Stanisław Lem, Walter M. Miller jr., John Brunner, and Paolo Bacigalupi.